The Fetal Region-specific Optimized Growth Standard (FROGS)-A fetal and birthweight centile calculator validated in a national population. - Natasha L Pritchard; Stephen Tong; Teresa MacDonald; Elizabeth McCarthy; Lisa Hui; Michael Bethune; Hannah G Gordon; Roxanne Hastie; Emerson Keenan; Michael Permezel; Susan P Walker; Anthea C Lindquist (PLoS Medicine)
Background There is no universally agreed upon obstetric growth standard for use during pregnancy. We aimed to design a simple novel growth standard, which incorporates key beneficial features identified in prior research. Methods and findings We developed the Fetal Region-specific Optimized Growth Standard (FROGS), then validated it following International Federation of Gynaecology and Obstetrics (FIGO) guidelines. FROGS follows the shape of the fetal (ultrasound-based) Hadlock curve. It is region-specific; allowing adjustment for the mean birthweight and standard deviation of babies born at term in the local population where it will be applied. It provides an exact centile for each gestational day (rather than rounding off by weeks) and is optionally adjustable for fetal sex. Further, FROGS provides an 'estimate range' for the estimated fetal weight centile, assuming a 10% ultrasound measurement error. Following development, we validated FROGS in a retrospective cohort study by comparing its ability to identify small babies with an increased risk of adverse perinatal outcomes to four charts in current use: (1) population birthweight chart (Australian Institute of Health and Welfare, AIHW chart); (2) Hadlock's 1991 fetal chart; (3) Mikolajczyk's global fetal and birthweight centile chart; and (4) INTERGROWTH-21st fetal growth standards. To do this, we identified infants classified as small for gestational age (<10th centile) by each chart. We then identified non-overlapping <10th centile populations, i.e., infants classified as small by one chart, but not another. We compared rates of stillbirth and adverse perinatal outcomes between the non-overlapping populations. All charts except INTERGROWTH classified similar proportions of infants as <10th centile (10.4% FROGS, 9.3% AIHW, 11.1% Hadlock, 10.9% global, 4.4% INTERGROWTH). Of the three charts that classified similar proportions as <10th centile, infants classified by FROGS were at the highest risk of adverse perinatal outcomes. The infants classified as <10th centile by only FROGS had significantly increased relative risk (RR) of stillbirth, compared to the infants classified as <10th centile by only AIHW (RR 13.1, 95% CI 6.5-26.5), only Hadlock (RR 2.1, 95% CI 1.28-3.56) or only the global chart (RR 1.54, 95% CI 1.00-2.37). The FROGS chart outperformed these three charts in identifying infants at risk of other adverse perinatal outcomes associated with being small for gestational age, such as neonatal intensive care admission, Apgar scores <7 at 5 min, and operative (instrumental) vaginal birth for suspected fetal compromise. The cohort of infants classified as small for gestational age by INTERGROWTH was, in size and risk, closer to the cohort classified as <3rd centile by FROGS (3.4% of infants <3rd). This study is limited in that it retrospectively assesses birthweight, which may have different implications to a prospective evaluation of estimated fetal weight. Conclusions Compared to currently used charts, the Fetal Region-specific Optimized Growth Standard outperforms existing charts that classify a similar proportion of infants as small for gestational age in identifying small infants at increased risk of stillbirth and other serious perinatal outcomes. The FROGS centile algorithm is simple and transparent. It has the potential to be adapted to other local populations, or applied to clinical and research settings globally.